Falciparum malaria in the north of Laos: the occurrence and implications of the Plasmodium falciparum chloroquine resistance transporter (pfcrt) gene haplotype SVMNT. - Dittrich, S; Alifrangis, M; Stohrer, J; Thongpaseuth, V; Vanisaveth, V; Phetsouvanh, R; Phompida, S; Khalil, I; Jelinek, T (2005)
OBJECTIVE: The Pfcrt-gene encodes a transmembrane protein located in the Plasmodium falciparum digestive vacuole. Chloroquine resistant (CQR) strains of African and Southeast Asian origin carry the Pfcrt-haplotype (c72-76) CVIET, whereas most South American and Papua New Guinean CQR stains carry the SVMNT haplotype. METHOD: Eighty-eight samples from an area with reported in vivo Chloroquine and in vitro Amodiaquine-resistance were screened for the K76T mutation and their Pfcrt-haplotype (c72-76) using a new SSOP-ELISA. RESULTS: Hundred percent of the analysed samples showed the K76T mutation which is highly associated with in vivo drug failure. This very high rate of a CQR-marker is alarming in an area were CQ is still used as first line drug. The distribution of the three main Pfcrt-haplotypes was as follows: 68% CVIET, 31% SVMNT, 0% CVMNT. CONCLUSIONS: These data show, for the first time, the South American/PNG -haplotype (SVMNT) on mainland Southeast Asia. SVMNT-haplotype and others might be associated with a decreased efficacy of Amodiaquine and could therefore be potential markers for of amodiaquine resistance (AQR). If there is a correlation between AQR and the SVMNT-haplotype as suggested, 31% prevalence of a potential resistance marker is cause for concern.